Tunable Magnetic Heating in La0.51Sr0.49MnO3 and La0.51Dy0.045Sr0.445MnO3 Nanoparticles: Frequency- and Amplitude-Dependent Behavior - Mourad Smari; Monica Viorica Moisiuc; Mohammad Y. Al-Haik; Iordana Astefanoaei; Alexandru Stancu; Fedor Shelkovyi; Radel Gimaev; Julia Piashova; Vladimir Zverev; Yousef Haik (Nanomaterials)
The use of perovskite manganite nanoparticles in magnetic hyperthermia has attracted significant attention due to their tunable magnetic properties and high specific absorption rate (SAR). In this work, we present a combined experimental and theoretical investigation of the frequency- and amplitude-dependent magnetic heating behavior of La0.51Sr0.49MnO3 (LSMO) and Dy-doped La0.51Dy0.045Sr0.445MnO3 (DLSMO) nanoparticles. The nanoparticles were synthesized via the sol–gel method and characterized by XRD and SEM, while SAR values were experimentally evaluated under varying magnetic field strengths (60–120 Oe) and frequencies (150–300 kHz). In parallel, theoretical modeling based on Néel and Brownian relaxation mechanisms was employed to predict SAR behavior as a function of particle size, magnetic anisotropy, and fluid viscosity. The results reveal that Dy doping enhances magnetic anisotropy, which modifies the relaxation dynamics and leads to a reduction in SAR. The model identifies the optimal nanoparticle size (~18–20 nm) and ferrofluid viscosity to maximize heating efficiency. This combined approach provides a comprehensive framework for designing and optimizing perovskite-based nanoparticles for magnetic hyperthermia applications.